Evaluating the influence of winemaking practices on biogenic amine production by wine microorganisms - Smit, Anita Yolandi (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2007.